2020
DOI: 10.1111/spsr.12390
|View full text |Cite
|
Sign up to set email alerts
|

Voters’ Knowledge of Their Representatives: The Direct and Conditioned Effects of Parliamentary Work

Abstract: This article examines factors that influence voters’ knowledge of their representatives, a key element in securing the responsiveness and accountability of parliamentarians. We argue that the parliamentary work of MPs (Members of Parliament) benefits incumbents through increased name recall, and that this relationship is conditional on: the incumbents’ candidacy; the voters’ political competence; and their ideological proximity with their representatives. Combining data on French MPs’ activities with a 2007 CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…The strategic allocation of rapporteurships and/or their more obscure status might offer a tentative explanation for this null finding. Other work has found some ambivalent effects of rapporteurships on voting behaviour (François and Navarro 2020).…”
Section: Data Analysis and Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The strategic allocation of rapporteurships and/or their more obscure status might offer a tentative explanation for this null finding. Other work has found some ambivalent effects of rapporteurships on voting behaviour (François and Navarro 2020).…”
Section: Data Analysis and Resultsmentioning
confidence: 97%
“…Higher attendance levels are also prized by voters (Däubler et al, 2018). There is further evidence that information on legislative productivity does get out, since knowledge of parliamentarians increase with legislative productivity (François and Navarro, 2020). The flourishing of web pages ranking politicians according to their productivity in the legislature is a case in point (Edwards et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the work in parliament ought to have only a limited impact on an MP's notoriety, inciting him or her to invest time and resources in his or her district in order to cultivate the personal vote required for his or her re-election (Brouard et al, 2013;Brouard and Kerrouche, 2014). This picture has been, however, recently challenged (François and Navarro, 2020), showing that work in parliament does influence an MP's name recognition. France is thus a good case for assessing how MPs take into consideration the demands of their constituents in weak and party-centred legislatures.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Comparative literature has shown that the incentives emanating from the electoral system can even be greater than in many proportional systems (Pilet et al, 2012). The recent literature on the electoral incentives thus challenges the conception of the Assemblé Nationale as a least likely case for district-oriented responsiveness and decentralised personalisation (François and Navarro, 2020). This leads to a paradoxical situation.…”
Section: A Weak and Party-centred Legislature: The Case Of Francementioning
confidence: 99%
See 1 more Smart Citation